STATUS TANAH DALAM RANGKA PEMBENTUKAN DESA - Fx Sumarja (Universitas Lampung, 2007)
This study aims to determine: setting the status of the land in order to establish the village, the authority of local government in the formation of the village, the significance of soil status the establishment of a village, and the policy of the Government of the Regency / City in Lampung province in the formation of the village related to land status. The analysis showed that the regency / municipal government has the authority to conduct the formation of the village which must be incorporated into regional regulation. The status of the land does not get the settings explicitly in the legislation. Keywords: Establishment of Village, Land Status